2018
DOI: 10.1093/ibd/izy060
|View full text |Cite
|
Sign up to set email alerts
|

The Artificial Sweetener Splenda Promotes Gut Proteobacteria, Dysbiosis, and Myeloperoxidase Reactivity in Crohn’s Disease–Like Ileitis

Abstract: Splenda promoted gut Proteobacteria, dysbiosis, and biochemical MPO reactivity in a spontaneous model of (Bacteroidetes-rich) ileal CD. Our results indicate that although Splenda may promote parallel microbiome alterations in CD-prone and healthy hosts, this did not result in elevated MPO levels in healthy mice, only CD-prone mice. The consumption of sucralose/maltodextrin-containing foods might exacerbate MPO intestinal reactivity only in individuals with a pro-inflammatory predisposition, such as CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
131
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 179 publications
(146 citation statements)
references
References 65 publications
6
131
0
9
Order By: Relevance
“…f ) Visualization of rich community composition for the bacteria present in the microdroplet solution used to spray germ-free mice. Parallel lanes plating method 13 . g ) Visualization of bacteria-contained on macro/micro-droplets on a quarter of a Petri dish.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…f ) Visualization of rich community composition for the bacteria present in the microdroplet solution used to spray germ-free mice. Parallel lanes plating method 13 . g ) Visualization of bacteria-contained on macro/micro-droplets on a quarter of a Petri dish.…”
Section: Resultsmentioning
confidence: 99%
“…All respiratory viruses need liquid suspensions/droplets to remain infective for long periods of time (vs. dry), and to contaminate susceptible individuals 12 . Therein, using a bacterial-suspension spray simulation model of droplet ejection (mimicking a sneeze) 11 , and a Parallel Lanes Plating method 13 , herein we quantified the extent by which widely available clothing fabrics could protect germ-free animals on the other side of the textile-barrier (simulating a properly worn mask) from contamination by the microbes contained in micro-droplets. In short, the reported experiment was conducted with eighteen 9-week-old germ-free (Swiss Webster) mice (males:females, 1:1), which were individually allocated to 18 germ-free cages, for repeated exposure to a cloud of micro-droplets.…”
Section: Methodsmentioning
confidence: 99%
“…Gut dysbiosis has been widely believed to cause the metabolic syndrome and other obesity-related comorbidities, but studies that put forth this hypothesis have failed to apply all the causality establishment criteria [Janket et al, 2018]. In a murine model, mice fed Splenda (sucralose and maltodextrin) increased proteobacteria, dysbiosis, and myeloperoxidase reactivity [Rodriguez-Palacios et al, 2018]. However, the increase in proteobacteria could be filling the voids generated by decreased Firmicutes (i.e., streptococci).…”
Section: Xylitol Intake and Gut Dysbiosismentioning
confidence: 99%
“…deserve emphasis.As reflected by the literature reviewed and the misconceptions documented in our survey, little is known 302 about the effect of time of year/season on mouse research heterogeneity 3,63,70. Since it is almost impossible to control 303 for seasonal variation within long-term, or multiple short-term experiments spanning over several seasons, it is 304 important to take measures to improve measures taken to improve study variation/reproducibility over time (e.g., food 305 batch, inter-experiment IsPreFeH).…”
mentioning
confidence: 95%
“…Of concern, the 'time of year/season' was the least important aspect believed to influence 178 the microbiome (ranked 15 th ); however, we have shown that cross-sectional metagenome experiments conducted in 179 separate seasons produce contrasting results when assessing the role of Helicobacter spp. in spontaneous Crohn's 180 disease-like ileitis in mice, 3 implying that repeating experiments across seasons may yield unreproducible results 181 over time.…”
mentioning
confidence: 99%